ON THE REFORMING OF NATIONAL HIGHER EDUCATION SYSTEM - V. S. SENASHENKO (Moscow Polytechnic University, 2017)
The article considers the main stages of the reform of the Russian higher education system. It discusses the reasons why the ongoing educational reforms have not led to an improvement in the quality of higher education. Among them are the unreasonable use of foreign experience, the introduction of values based on material and consumer standards adapting the education system to market laws and the absence of a coherent national strategy for the development of higher education. The article also underlines that the further promotion of educational reforms in a positive direction is hardly possible without taking into account the views of the higher school community.